PENGETAHUAN GIZI IBU, POLA MAKAN, ASUPAN ZAT GIZI DAN STATUS GIZI ANAK DENGAN AUTISM SPECTRUM DISORDER (ASD) - Redy Sopiandi (UHAMKA PRESS, 2017)
Implementation of gluten-free casein-free diet considered to alleviate the condition ofchildren with autism. However, this diet began to be associated with a risk of overweight inchildren with Autism Spectrum Disorder (ASD). The general objective of this study was todetermine the relationship between maternal nutritional knowledge, diet, energy intake andmacro-nutrients with the nutritional status of children with autism in the School of CitraAnindya Bintaro, South Tangerang. In this study, the method used was the cross sectionaldesign. Sampling method with purposive sampling with the total number of subjects were 32.Data analysis technique with Chi-Square statistical test. Based on this research, there wassignificant correlation (p<0,05) between diet, energy intake, and fat intake with nutritionalstatus of autism children. There was no significant correlation (p>0,05) between maternalnutritional knowledge, protein intake and carbohydrate intake with nutritional status ofchildren with autism.